2022
DOI: 10.17816/clinpract108920
|View full text |Cite
|
Sign up to set email alerts
|

A diversion stoma after anterior resection for rectal cancer

Abstract: The article covers the problem of forming diverting stoma during resections of the rectum with primary anastomosis. The incidence of rectal cancer tends to increase, and surgical resection remains the main method of treatment. Anastomotic leakage significantly increases postoperative mortality. The most effective way to prevent severe complications is the formation of a diverting stoma. However, the indications, the choice of a specific technique and the timing of stoma elimination are not clearly defined. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
0
0
Order By: Relevance
“…The literature indicates that the rate of ileostomy after rectal resection ranges from 14% to 100% [ 10 ]. Furthermore, these patients must also undergo surgery to close the ileostomy, which carries many risks [ 22 , 25 - 27 ]. The research by Brisinda et al showed that ileostomy did not necessarily help reduce the anastomotic leak rate [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The literature indicates that the rate of ileostomy after rectal resection ranges from 14% to 100% [ 10 ]. Furthermore, these patients must also undergo surgery to close the ileostomy, which carries many risks [ 22 , 25 - 27 ]. The research by Brisinda et al showed that ileostomy did not necessarily help reduce the anastomotic leak rate [ 19 ].…”
Section: Discussionmentioning
confidence: 99%